What factors predict the need for further intervention following corticosteroid injection of Morton's neuroma?. Issue 1 (March 2016) - Mahadevan, Devendra; Salmasi, Mohammad; Whybra, Nicola; Nanda, Anika; Gaba, Suchi; Mangwani, Jitendra
Highlights: 51% of cases with Morton's neuroma required further intervention within 2 years of receiving an ultrasound-guided corticosteroid injection. Larger neuromas and younger patients were predictors of the need for further intervention but not gender. The distribution of concomitant forefoot pathology and ipsilateral neuromas were similar in the group that received further treatment and the group that did not. Abstract: Background: This study investigated factors that may predict the need for Morton's neuroma (MN) to undergo further treatment within 2 years of a single ultrasound-guided corticosteroid injection. Methods: A retrospective study was undertaken over a three-year period. The data was stratified into two groups: Group A – did not receive further intervention and Group B – received further treatment. We investigated age, gender, neuroma size and presence of other forefoot pathology or ipsilateral neuromas. Results: 54 patients (57 feet) were reviewed. 29 feet (51%) required further treatment within 2 years (11 repeat injections, 18 surgical excisions). Binary logistic regression showed that larger neuromas ( p = 0.011) and younger patients ( p = 0.007) predicted the need for further intervention but not gender ( p = 0.272). The distribution of concomitant forefoot pathology and ipsilateral neuromas were similar between the two groups. Conclusion: Size and age appear to be predictors for further treatment of MN within 2 years of corticosteroid injection.